The role of gill raker number variability in adaptive radiation of coregonid fish - Kahilainen, Kimmo; Siwertsson, Anna; Gjelland, Karl Øystein; Knudsen, Rune; Bøhn, Thomas; Amundsen, Per-Arne (Evolutionary Ecology, 2010)
Source at https://doi.org/10.1007/s10682-010-9411-4 . Gill raker divergence is a general pattern in adaptive radiations of postglacial fish, but few studies have addressed the adaptive significance of this morphological trait in foraging and eco-evolutionary interactions among predator and prey. Here, a set of subarctic lakes along a diversifying gradient of coregonids was used as the natural setting to explore correlations between gill raker numbers and planktivory as well as the impact of coregonid radiation on zooplankton communities. Results from 19 populations covering most of the total gill raker number gradient of the genus Coregonus , confirm that the number of gill rakers has a central role in determining the foraging ability towards zooplankton prey. Both at the individual and population levels, gill raker number was correlated with pelagic niche use and the size of utilized zooplankton prey. Furthermore, the average body size and the abundance and diversity of the zooplankton community decreased with the increasing diversity of coregonids. We argue that zooplankton feeding leads to an eco-evolutionary feedback loop that may further shape the gill raker morphology since natural selection intensifies under resource competition for depleted prey communities. Eco-evolutionary interactions may thus have a central role creating and maintaining the divergence of coregonid morphs in postglacial lakes.